Les grandes tendances de l’alternance des langues dans la presse écrite d’Algérie - Mourad Bektache (Multilinguales)
French as it is spoken and read in Algeria, presents very important lexical variations that led us to inquire about some of these characteristics in the Algerian written press. We are more precisely interested in code switching and the discursivo-argumentative mechanisms which, take part in the modeling of the French employed in four newspapers namely, El Moudjahid, El Watan, La Tribune, Liberté. The analysis of the corpus revealed that the alternation of the Arabic, Berber and French languages, as it appears in these four daily newspapers, obeys to discursive strategies used by journalists in order to create a communicational universe specifically Algerian.